Value Distribution of General Dirichlet series. VI - Laurinčikas, A. (Nonlinear Analysis: Modelling and Control, 2005)
In the paper a limit theorem in the sense of weak convergence of probability measures on the complex plane for a new class of general Dirichlet series is obtained.